Meningkatkan Hasil Belajar Siswa Fase F Kelas XI Materi Martyria melalui Model PBL Berbantuan YouTube di SMA Bintang Laut Teluk Dalam - Jansen Norbertus Dachi; Nerita Setianingtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to explore and measure student learning outcomes in the Catholic Religion subject on the Martyria material, which is one of the five duties of the Church, through the Problem Based Learning learning model assisted by YouTube videos. This research is a classroom action research involving 32 students in class XI -IPA 4 of SMA Swasta Katolik Bintanglaut Telukdalam in the 2023/2024 academic year. Data were collected from observations and assessments carried out in each cycle, then analyzed quantitatively-descriptively. The results of the classroom action research showed that the results of the summative test in Cycle I were only 20 students who completed it with a percentage of 62.5%. Furthermore, in cycle II, the results of the summative test were 30 students who completed it with a percentage of 93.75% and the results of observations of student activities from a comparison of scores from two meetings in cycle I were 63.47%, while in two meetings in cycle II the results of observations of student activities obtained a percentage of 85.15%. Thus, the Problem Based Learning learning model assisted by YouTube videos can improve student learning outcomes.